INTERPRETATION OF ECOTOURISM BY TOUR GUIDES ON BUTTERFLY TOURIST ATTRACTIONS IN BALI - Apriska, Ni Kadek Siska; Raka Dalem, Anak Agung Gde; Suartini, Ni Made (SIMBIOSIS, 2022)
Research on ecotourism interpretation by tourist guides on butterfly attractions in Bali has been carried in 2020-2021.  Objectives of this research were to find out the type of interpretation, means (tools) of interpretation and the quality of interpretation given to tourists. The method of data collection was by accidental sampling, conducting interviews, direct observation in the field, distributing questionnaires and examining documents. Data analysis was carried out quantitatively and qualitatively. The results obtained indicated that the types of interpretation applied by tour guides on butterfly parks in Bali were 9 types, namely guided tour, point duty, roving interpretation, presentation, demonstration, living history, interactive, talk and drama. There were 10 types of interpretation facilities utilized namely print, self guiding program, interpretive panel, use of audio tape, exhibit, visitor center, museum, computer, laser disc and observation hides. The quality of the interpretation by the tour guides in general could be classified as good. Based on this finding, there were some points need to be improved by the butterfly tour guides.